Development of a ready-to-drink banana peanut flavored beverage - Tagorda, Normielyn Sebastian; Azanza, Ma. Patricia V. (1997.)
The objective of this study is to develop a ready-to-drink banana flavored peanut beverage. The product is a possible cheap and nutritious alternative snack drink. The first phase of the sudy dealt with the incorporation of acceptable flavor and color concentrations to the peanut beverage. The test banana flavor concentrations used were: 0.0, 0.1, 0.5 and 1.0%. The samples were subjected to sensory evaluation for descriptive acceptability test. The sample with 0.1% banana flavor concentrate was found most acceptable. A need to add color to the banana flavored peanut beverage was determined. Pre-testing was done using the Roche Yolk Color Fan to determine what banana yellow colors will be incorporated to the peanut beverage. The McCormick color concentrations were: 0.0, 0.02, 0.10 and 0.20%. The samples were subjected to descriptive evaluation test and the test sample with 0.1% color concentration was found most acceptable. The second phase of the study involved storage stability tests. Quality assessment of the banana flavored peanut beverage was done through microbiological and physico-chemical tests. The Total Plate Count (TPC) of the product increased from 7.8 x 10^3 to >3.0 x 10^7 cfu/ml after 10 days of storage at 5°C. The Yeast and Mold Count (YMC) increased from <10 to 3.1 x 10^2 cfu/ml after 10 days of storage. The Aspergillus flavus and A. parasiticus Count (AFPC) was <100 cfu/ml throughout the storage period of 10 days. The physico-chemical tests included tests on color, pH and %SS. The color and %SS of the banana flavored peanut beverage did not change during the course of storage stability study. The pH decreased from 7.1 to 6.0 after 10 days of storage. The third phase of the study involved cost analysis. The actual cost of the banana flavored peanut beverage in polyethylene bottle is P4.84 per 250 ml and the selling price was calculated to be P5.32 per 250 ml with 10% mark-up. The banana flavored peanut beverage is inexpensive compared to the existing commercial milk beverages like Magnolia Fresh Milk which costs P13.50 per 250 ml.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Beverages